Transmission of synovial sarcoma from a single multi-organ donor to three transplant recipients: case report - Jian Zhang; Yang Yang; Ye Tian; Ruifang Xu; Jun Lin (BMC, 2021)
Abstract Background Transmission of malignancy is a notable problem that cannot always be absolutely predicted at the time of transplantation. In particular, donor-derived transmission of synovial sarcoma in solid-organ transplantation is a rare but catastrophic event. Case presentation We are the first to report three cases of synovial sarcoma transmitted from a single multi-organ donor in China. The donor died of respiratory failure caused by an intrathoracic tumor, which was diagnosed as benign at the time of donation. All three recipients developed synovial sarcoma 3-13 months after transplantation; all three cases were confirmed to be donor transmitted. The liver transplant recipient died of tumor metastasis after partial-allograft hepatectomy. The two renal-transplant recipients survived after comprehensive therapy, including allograft nephrectomy, withdrawal of immunosuppressants and targeted therapy with anlotinib. Conclusions This report highlights the importance of detailed donor assessment, close follow-up and timely treatment of unexpected donor-transmitted malignancy. Although pathology is the most important evidence for the exclusion of donors for malignant potential, it should be combined with tumor type, tumor size and speed of growth. Organs from donors with malignant potential should be discarded. Allograft nephrectomy should be considered after confirmation of renal-allograft synovial sarcoma. Anlotinib for synovial sarcoma seems to be effective and well tolerated during long-term follow-up.